The effect of different animated brand logos on consumer response —— an event-related potential and self-reported study. (June 2023) - Peng, Minjing; Liang, Min; Huang, Haiyang; Fan, Jiajia; Yu, Lidan; Liao, Jianjin
Abstract: Animation is a design element that has "eye-catching" appeal in the consumer attention market. Businesses invest significant resources to incorporate animated elements in the design of brand logos. Against this background, this study investigated the consumer's cognitive process responding to brands that included two types of animated logos (agent animation vs. object animation). Specifically, event-related potentials were utilized to compare behavioral and electrophysiological activities under two primary types of animated logo stimuli. Behavioral data showed that participants spent less time making preference decisions related to agent animation than to object animation. Neurophysiological data demonstrated that agent animation increased participants' attentional resources (stronger N100 and P300 amplitudes) and improved their assessment of brand attitude as compared to object animation (higher late positive potential amplitude). Additional self-reported data confirmed that participant attention investment, perception of animacy, and brand attitude were promoted by agent condition more than by object condition. The study's findings offer fresh evidence from a neurocognitive standpoint for the animation influence mechanism on brand logos, which may provide businesses with a significant physiological objective indicator for designing animated brand logos that gauge consumer attitude scientifically. Highlights: Investigated consumer response to animated logo types: agent/object animation. The event-related potentials method was used to examine consumers' neural responses. Agent condition promoted greater attention, animacy perception, and brand attitude. Subjective and objective data confirm the cognitive process of animated logo.